Answer:
To find f-¹(x) of f(x) equate f(x) to y
That's
f(x) = y
So we have
Next interchange the variables that's x becomes y and y becomes x
That's
Next make y the subject
Cross multiply
We have
4y - 7 = 10x
Move -7 to the right side of the equation
4y = 10x + 7
Divide both sides by 4
We have the final answer as
So
Hope this helps you
Let's look at the corresponding ratios:
And we see that the three aren't equal.
Hence, $\Delta ABC$ and $\Delta EDC$ are not similar.
Answer:
Step-by-step explanation:
Solution by substitution method
3x+5y=7
and 4x-y=5
Suppose,
3x+5y=7→(1)
and 4x-y=5→(2)
Taking equation (2), we have
4x-y=5
⇒y=4x-5→(3)
Putting y=4x-5 in equation (1), we get
3x+5y=7
⇒3x+5(4x-5)=7
⇒3x+20x-25=7
⇒23x-25=7
⇒23x=7+25
⇒23x=32
⇒x=32/23
→(4)
Now, Putting x=32/23
in equation (3), we get
y=4x-5
⇒y=4(32/23)-5
⇒y=(128-115)/23
⇒y=13/23
∴y=13/23 and x=32/23
Answer:
its sophisticated but answer is 3
Step-by-step explanation:
you have to dive deep into it and research
Answer:
-5
Step-by-step explanation:
3x+7=-8
3x+7-7=-8-7
3x=-15
3x/3=-15/3
x= -5